Gap Junctional Coupling with Cardiomyocytes is Necessary but Not Sufficient for Cardiomyogenic Differentiation of Cocultured Human Mesenchymal Stem Cells123. (15th May 2012) - Ramkisoensing, Arti A.; Pijnappels, DaniëL A.; Swildens, Jim; Goumans, Marie José; Fibbe, Willem E.; Schalij, Martin J.; de Vries, Antoine A.F.; Atsma, Douwe E.
Abstract: Gap junctional coupling is important for functional integration of transplanted cells with host myocardium. However, the role of gap junctions in cardiomyogenic differentiation of transplanted cells has not been directly investigated. The objective of this work is to study the role of connexin43 (Cx43) in cardiomyogenic differentiation of human mesenchymal stem cells (hMSCs). Knockdown of Cx43 gene expression (Cx43↓) was established in naturally Cx43‐rich fetal amniotic membrane (AM) hMSCs, while Cx43 was overexpressed (Cx43↑) in inherently Cx43‐poor adult adipose tissue (AT) hMSCs. The hMSCs were exposed to cardiomyogenic stimuli by coincubation with neonatal rat ventricular cardiomyocytes (nrCMCs) for 10 days. Differentiation was assessed by immunostaining and whole‐cell current clamping. To establish whether the effects of Cx43 knockdown could be rescued, Cx45 was overexpressed in Cx43↓ fetal AM hMSCs. Ten days after coincubation, not a single Cx43↓ fetal AM hMSC, control adult AT MSC, or Cx43↑ adult AT mesenchymal stem cell (MSC) expressed α‐actinin, while control fetal AM hMSCs did (2.2% ± 0.4%, n = 5, 000). Moreover, functional cardiomyogenic differentiation, based on action potential recordings, occurred only in control fetal AM hMSCs. Of interest, Cx45 overexpression in Cx43↓ fetal AM hMSCs restored their ability to undergo cardiomyogenesis (1.6% ± 0.4%, n = 2, 500) in coculture with nrCMCs. Gap junctional coupling is required for differentiation of fetal AM hMSCs into functional CMCs after coincubation with nrCMCs. Heterocellular gap junctional coupling thus plays an important role in the transfer of cardiomyogenic signals from nrCMCs to fetal hMSCs but is not sufficient to induce cardiomyogenic differentiation in adult AT hMSCs. STEM CELLS 2012;30:1236–1245